Pengetahuan Mistis dalam Konteks Islam dan Filsafat Ilmu Pengetahuan - Hambali Hambali (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2011)
The mystical knowledge such as about jinn, Satan, Doomsday, dying, punishment after life, amenity in the hereafter and others cannot be rationally and empirically pursued. Etymologically, Encyclopedia of Philosophy defines knowledge as a true belief. This article is aimed to discover the mystical knowledge in Islam as well as in philosophy. The mystical knowledge is attained by feeling and heart. The mystical truth in Islam can be pursued through tasawuf. The mystical knowledge from philosophical is ontologically, epistemologically, and axiological can be perceived. The knowledge is very subjective. A black mystic or usually called a black magic is practiced for evilness while the white one is practiced for goodness.